2021
DOI: 10.1007/s41134-021-00170-4
|View full text |Cite
|
Sign up to set email alerts
|

Social Work Practice: Accounting for Double Injustices Experienced by Women Under the Confluence of Covid-19 Pandemic and Climate Change Impacts in Nyanga, Zimbabwe

Abstract: In this paper, the researchers argue that the repercussions of the Coronavirus Disease 19 pandemic are taking a toll on rural women, not as a new phenomenon, but as an amplifier for their historical calamities dovetailed by climate change. The declaration of COVID-19 as a global pandemic by the World Health Organisation ignited widespread pronouncements of national state of disasters in various countries around the globe including Zimbabwe. Subsequently, like other countries, Zimbabwe followed the precautiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 42 publications
0
15
0
Order By: Relevance
“…It is worth mentioning that 'COVID-19 and the associated terms/keywords were not included in any cluster, meaning that the number of works in this domain with a connection to the COVID-19 pandemic is still significantly low, even though there are works on climate change-gender without connection to leadership/empowerment, e.g., [105][106][107].…”
Section: Bibliometric Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…It is worth mentioning that 'COVID-19 and the associated terms/keywords were not included in any cluster, meaning that the number of works in this domain with a connection to the COVID-19 pandemic is still significantly low, even though there are works on climate change-gender without connection to leadership/empowerment, e.g., [105][106][107].…”
Section: Bibliometric Analysismentioning
confidence: 99%
“…One such global emergency is COVID-19 and its impacts. The pandemic unveiled and further amplified existing climate change vulnerabilities, including those related to gender inequalities [106,126,127]. Furthermore, there has been a concern that the pandemic might undermine actions taken towards climate change mitigation and reduction of gender imbalances [128][129][130].…”
Section: Stronglymentioning
confidence: 99%
“…Since its development, the SVT has been applied across various contexts, from hazards and natural disasters studies to more recent ones, such as the COVID-19 pandemic. For example, Nyahunda et al [ 30 ] adopted the SVT to investigate how climate change can have adverse impact on rural women in Zimbabwe during the pandemic. The study found that social vulnerability factors, such as gender inequalities and social exclusion, aggravated the catastrophic consequences (e.g., food insecurities and lack of access to healthcare) suffered by rural women and caused by climate change.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The mechanism offered in The Charter of the UN is an indication that a peaceful mechanism can be carried out and is considered detrimental during Covid-19 (Nyahunda et al, 2021). Through the mechanism of mediation, investigation/conciliation, including officers under the UN General Assembly mechanism, it is hoped that non-judicial efforts can still be an option that would be chosen by the parties.…”
Section: Article Historymentioning
confidence: 99%